ISLAMISASI KONSEP KEBAHAGIAAN MENURUT BARAT - Umam, Khoirul; Isa, Annas Muhammad (Universitas Al-Amien Prenduan, 2024)
AbstractThe concept of happiness is a complex concept among experts who measure the well-being of a person's life, in terms of their happiness and life satisfaction. Of course, Western and Muslim philosophers have many differences of opinion in various aspects, including in the field of science. because of the difference in their worldview that distinguishes the understanding between philosophers. The purpose of this research is to incorporate the Islamic worldview into aspects of science so as to be able to present insight and knowledge and become an acceptable psychological solution, not only accepted by Muslims but also acceptable to the general public. The type of research in this study uses qualitative research methods using a literature study approach. The results of this study indicate that the Islamic worldview in achieving happiness, religion directs humans to have the primacy of reason and intellect. The virtue of reason encourages humans to think and learn many things, reason is also the one who can think about the great favours he receives from God, the glory and the invaluable height so that he is free from humiliation and part of the perfection of reason is his preference for choosing noble behaviour. humans must optimise their minds and always maintain sincerity of heart, and strive to always put their trust in God. So, if a person has the pleasure of doing good because of his habit and hates disobedience, then he has reached the perfection of physical and mental happiness.